A summer of Kings - Nolan, Han (Harcourt, 2006)
Over the course of the summer of 1963, fourteen-year-old Esther Young discovers the passion within her when eighteen-year-old King-Roy Johnson, accused of murdering a white man in Alabama, comes to live with her family.